Women’s Movement in Late 1880s and 1890s in Britain: A Stagnation Era or a Leap Forward? - E. O. Naumenkova (Научный диалог, 2025)
This study examines the women’s movement in Britain during the late 1880s and 1890s. The sources include periodicals, publicist writings, memoirs, contemporary recollections, and transcripts of British parliamentary sessions. The paper challenges extreme historiographical perspectives that view the 1890s as either a period of decline for the women’s movement or, conversely, a time of breakthrough. The author concludes that this period was characterized by gradual development, marked by both successes and setbacks. On one hand, the social composition and organizational structure of the movement expanded, the number of parliamentary supporters increased, and women’s roles in electoral campaigns and local governance grew. By the late 1880s, women began to be recognized as a significant political force. On the other hand, the primary goal of achieving voting rights remained unfulfilled; the number of women working within electoral structures and campaigns was relatively small compared to the overall population, and repeated schisms within the movement indicated a certain weakness during the first half of the examined period. The analysis delves into the reasons motivating women's participation in activism, raises questions about strategies for securing suffrage, and discusses the challenges faced by suffragists. It is emphasized that during this time, disillusioned with constitutional methods of campaigning for enfranchisement, suffragists gradually leaned toward more militant approaches.